2014
DOI: 10.1021/jo500557w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Origins of Switchable Regioselectivity of Palladium- and Nickel-Catalyzed Allene Hydrosilylation with N-Heterocyclic Carbene Ligands: A Theoretical Study

Abstract: The mechanisms and origins for the Pd- and Ni-catalyzed regioselective hydrosilylation of allene have been investigated by means of density functional theory (DFT) calculations. The free-energy profiles of Pd- and Ni-catalyzed reactions with small and bulky N-heterocyclic carbene (NHC) ligands are calculated to determine the mechanism for regioselectivities. The calculation results show that different metals (Ni vs Pd) lead to regiochemical reversals for the hydrosilylation of allene. The allylsilane is the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 89 publications
(44 reference statements)
1
34
0
Order By: Relevance
“…It is known that palladium‐catalyzed reactions of hydrosilanes are involved in a number of important synthetic methodologies, and the oxidative addition of palladium(0) species to the Si−H bond is considered to be an important fundamental step. Similar to palladium‐ or platinum‐catalyzed hydrosilylation of alkynes and alkenes with hydrosilane, hydrosilane is initially coordinated to the palladium(0) catalyst to form a characteristic Pd 0 ‐η 2 ‐hydrosilane complex ( Cplx1 ) with a stabilization energy of 8.9 kcal mol −1 . Then, oxidative addition of palladium(0) complex O to the Si−H bond of 2 a proceeds smoothly with a low free energy barrier of 2.5 kcal mol −1 via TS OA , leading to a R 3 Si−Pd II −H intermediate ( A ), in which the hydrogen atom is cis to the silyl group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that palladium‐catalyzed reactions of hydrosilanes are involved in a number of important synthetic methodologies, and the oxidative addition of palladium(0) species to the Si−H bond is considered to be an important fundamental step. Similar to palladium‐ or platinum‐catalyzed hydrosilylation of alkynes and alkenes with hydrosilane, hydrosilane is initially coordinated to the palladium(0) catalyst to form a characteristic Pd 0 ‐η 2 ‐hydrosilane complex ( Cplx1 ) with a stabilization energy of 8.9 kcal mol −1 . Then, oxidative addition of palladium(0) complex O to the Si−H bond of 2 a proceeds smoothly with a low free energy barrier of 2.5 kcal mol −1 via TS OA , leading to a R 3 Si−Pd II −H intermediate ( A ), in which the hydrogen atom is cis to the silyl group.…”
Section: Resultsmentioning
confidence: 99%
“…Then, oxidative addition of palladium(0) complex O to the Si−H bond of 2 a proceeds smoothly with a low free energy barrier of 2.5 kcal mol −1 via TS OA , leading to a R 3 Si−Pd II −H intermediate ( A ), in which the hydrogen atom is cis to the silyl group. Owing to the trans influence of the silyl and hydrogen to the phosphine ligand, the stability of A is relative low. Intermediate A adopts a planar geometry, the main geometric parameters of which are quite close to the first stable mononuclear silyl palladium hydride reported by Fink and co‐workers with r (Pd−Si)=2.312 Å and r (Pd−P)=2.332/2.408 Å …”
Section: Resultsmentioning
confidence: 99%
“…357 The steric bulk of the ligand was found to determine whether the allene first is silylated (with bulky IPr) or hydrogenated (with IMes). Computational results obtained at the CPCM (THF)// B3LYP/6-31G(d)(LANL2DZ+d,f) level of theory indicated that Ni lowers the barriers for all reactions when compared to Pd (Scheme 26).…”
Section: Olefin Functionalizationmentioning
confidence: 99%
“…For one-to-one or two-to-two transformation, no correction was made. For two-to-one (or one-to-two) transformation, a correction of -2.6 (or 2.6) kcal/mol was made at the temperature of 298.15 K. These corrections have been applied in several earlier theoretical studies [45][46][47][48]. In this work, the entropy-corrected relative free energies were adopted to analyze the reaction mechanisms.…”
Section: Computational Detailsmentioning
confidence: 99%